ADAMTS13 gene; a novel splicing site mutation in a case with thrombotic thrombocytopenic purpura - Sepideh Zununi Vahed; Alessandra Cremaschi; Behzad Zaker; Seyed Sadroddin Rasi Hashemi; Mohammadreza Ardalan (Society of Diabetic Nephropathy Prevention, 2021)
A plasma protease, ADAMTS13, cleaves the von Willebrand factor (VWF) and its deficiency is associated with the pathogenesis of thrombotic thrombocytopenic purpura (TTP). According to the Human Gene Mutation Database (HGMD), about 150 mutations have been identified in the ADAMTS13 gene. A 23-year-old man, with hematuria and gingival bleeding was admitted to our University Hospital. Four years ago he was diagnosed with a TTP history. During these years, he was under intermittent plasma exchange. A blood sample was taken for genetic study. He effectively responded to one session of fresh frozen plasma replacement and plasma exchange. Genetic study indicated that this case carries two heterozygous mutations in ADAMTS13 gene; a novel splicing variant (c.2610+5G>A) and a nonsense p.Arg910X mutation that previously is reported to relate to TTP. The novel variant predicted to result in an aberrant ADAMTS13 transcript processing.